Molecular characterization of porcine Siglec-10 and analysis of its expression in blood and tissues. Issue 1 (January 2015) - Escalona, Z.; Álvarez, B.; Uenishi, H.; Toki, D.; Yuste, M.; Revilla, C.; del Moral, M. Gómez; Alonso, F.; Ezquerra, A.; Domínguez, J.
Highlights Generation of cell lines expressing porcine Siglec-10. Development of monoclonal antibodies to porcine Siglec-10. Porcine Siglec-10 is mainly expressed on B cells in blood and tissues, and at low levels on monocytes.